Landownership in Eastern Germany before the Great War a quantitative analysis - Eddie, Scott McNeil (Oxford University Press, 2008)
Who were the great landlords of eastern Germany? Scott Eddie analyses shifts in land ownership to identify these key figures in the country's history.